Moksha and Liberation - T A Aykara (Journal of Dharma, 1977)
World-bound in structure and Goal Oriented in nature, man constantly experiences the painful predicament of his being torn between the to-be and the not-yet in his daily lived-life. His existence is an extended polarity between actions already actua- lised and yet to be actualised. Rooted in time but destined for eternity, his factual fate is of finitude’ and often of futility that brings about a constitutive unsatisfactoriness (dubhba) in his very existential make up. At the core of his consciousness and at the heart of his being, man confronts an estranged situation.